Improving plant drought tolerance and growth under water limitation through combinatorial engineering of signalling networks. Issue 1 (26th July 2020) - Schulz, Philipp; Piepenburg, Katrin; Lintermann, Ruth; Herde, Marco; Schöttler, Mark A.; Schmidt, Lena K.; Ruf, Stephanie; Kudla, Jörg; Romeis, Tina; Bock, Ralph
Abstract: Agriculture is by far the biggest water consumer on our planet, accounting for 70 per cent of all freshwater withdrawals. Climate change and a growing world population increase pressure on agriculture to use water more efficiently ('more crop per drop'). Water‐use efficiency (WUE) and drought tolerance of crops are complex traits that are determined by many physiological processes whose interplay is not well understood. Here, we describe a combinatorial engineering approach to optimize signalling networks involved in the control of stress tolerance. Screening a large population of combinatorially transformed plant lines, we identified a combination of calcium‐dependent protein kinase genes that confers enhanced drought stress tolerance and improved growth under water‐limiting conditions. Targeted introduction of this gene combination into plants increased plant survival under drought and enhanced growth under water‐limited conditions. Our work provides an efficient strategy for engineering complex signalling networks to improve plant performance under adverse environmental conditions, which does not depend on prior understanding of network function.